In Vitro Antimicrobial Activity of the Siderophore Cephalosporin Cefiderocol against Acinetobacter baumannii Strains Recovered from Clinical Samples - Davide Carcione (MDPI AG, 2021)
Background: Cefiderocol is a siderophore cephalosporin that exhibits antimicrobial activity against most multi-drug resistant Gram-negative bacteria, including Enterobacterales, Pseudomonas aeruginosa, Acinetobacter baumannii, and Stenotrophomonas maltophilia. Methods: A total of 20 multidrug-resistant A. baumannii strains were isolated from 2020 to 2021, molecularly characterized and tested to assess the in vitro antibacterial activity of cefiderocol. Thirteen strains were carbapenem-hydrolysing oxacillinase OXA-23-like producers, while seven were non-OXA-23-like producers. Minimum inhibitory concentrations (MICs) were determined by broth microdilution, considered as the gold standard method. Disk diffusion test was also carried out using iron-depleted CAMHB plates for cefiderocol. Results: Cefiderocol MICs ranged from 0.5 to 1 mg/L for OXA-23-like non-producing A. baumannii strains and from 0.25 to >32 mg/L for OXA-23-like producers, using the broth microdilution method. Cefiderocol MIC90 was 8 mg/L. Diameter of inhibition zone of cefiderocol ranged from 18 to 25 mm for OXA-23-like non-producers and from 15 to 36 mm for OXA-23-like producers, using the diffusion disk method. A large variability and a low reproducibility were observed during the determination of diameter inhibition zone. Molecular characterization showed that all isolates presented the ISAba1 genetic element upstream the blaOXA-51. Among OXA-23-like non-producers, four were blaOXA-58 positive and two were negative for all the resistance determinants analyzed. Conclusions: Cefiderocol showed in vitro antimicrobial activity against both carbapenem-susceptible and non-susceptible A. baumannii strains, although some OXA-23-like producers were resistant. Further clinical studies are needed to consolidate the role of cefiderocol as an antibiotic against MDR A. baumannii.